PERLINDUNGAN ANAK DARI PERKAWINAN SIRI BERDASARKAN PASAL 20 UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Suardja, Tatang Odjo (Yustitia, 2019)
With the presence of a child born from a legal marriage (registered marriage) both parents have proven that the child is a legitimate biological child of his father and mother. The legal consequences if the marriage is not registered (commonly known as "perkawinan siri"), the status of children born from the marriage will be uncertain. This is because the marriage of both parents is only religiously valid according to Article 20 Number 35 of 2014 of the constitution regarding the child protection. In this research, the method used is a normative juridical approach with data collection techniques in the study of literature both primary legal materials, secondary legal materials, and tertiary legal materials. This study analyzed and described the protection of children from unregistered marriage (perkawinan siri) according to Article 20 Number 35 of 2014 of the constitution regarding the child protection and the government's role of protection of the children based on the law. The theory of justice contains a demand that people treat each other according to their rights and obligations. The treatment is indiscriminate or favoritism, but rather, all people are treated equally according to their rights and obligations. A person born from a marriage between a woman and a man does not rule out that someone who is born by a woman who has never married is still a child.